Phylogenetic and taxonomic analyses reveal three new records of Helvella in Türkiye - Terman, Şuheda Aldemi̇r; Akçay, Mustafa Emre; Dizkirici, Ayten (Phytotaxa, 2025)
In this study, morphological and molecular analyses of three newly collected saddle-like fungi confirm their classification within the genus Helvella L. from the eastern Türkiye. A three-locus phylogeny was constructed using the internal transcribed spacer (ITS) region, the translation elongation factor 1-alpha (TEF1-α), and the large subunit (LSU) of the ribosomal RNA gene. Phylogenetic analyses were performed using Maximum Likelihood (ML) and Bayesian Inference (BI) approaches. The phylogeny inferred from the concatenated dataset revealed three distinct clades. The Turkish Helvella species were distributed across the Elastica, Lacunosa and Acetabulum clades, identified as H. rivularis, H. sublactea, H. arcto-alpina, respectively. Both single-locus and multi-locus data provided informative results. In addition to phylogenetic analysis, detailed macro- and micro- features, along with illustrations, were provided for each studied species.